Limited Liability Company Individuals Are Quasi Legal Entities In the Concept of Legal Entities in Indonesia - Ramlan, Ramlan (Universitas Muhammadiyah Sumatera Utara, 2025)
This writing aims to see whether PT Perseroan is a legal entity or quasi legal entity. The type of research used is normative legal research with a statutory approach and a conceptual approach, and the nature of the research is explanatory and uses secondary data with primary legal materials UUCK and UUPT and is analyzed qualitatively. A company is said to be a legal entity if there are the following elements; having an association which in a broad sense is an association of people who feel they have a common interest based on an agreed agreement. Having a GMS organ as a decision maker, a Board of Directors as an organ that runs the PT and a Board of Commissioners that supervises the Board of Directors. A legal entity can carry out legal acts with the help of its organs consisting of humans. Humans and legal entities are both legal subjects, so that both are bearers of legal rights and obligations. In addition, a legal entity has assets that come from the income of its members and are separate from the personal assets of its members. A legal entity can also act independently and can carry out a legal act itself, so that a legal entity can sue and be sued in court. To obtain a legal entity, a company must obtain approval from the Minister of Law and Human Rights. Based on these elements, a PT Perseroan can be said to be a quasi legal entity.